Oliver Twist - "Dickens, Charles" (Maqbool Books: Lahore, 2010)
Charles Dickens's Oliver Twist is a seminal Victorian novel that explores the life of an orphan, Oliver, as he navigates the harsh realities of 19th-century London. After being born in a workhouse and subjected to abuse and neglect, Oliver runs away to London, where he falls into the clutches of Fagin, a criminal who trains children to become pickpockets. Through Oliver$1 (Bs journey$1 (Bmarked by encounters with characters like the kind Mr. Brownlow, the compassionate Nancy, and the menacing Bill Sikes$1 (BDickens critiques societal injustices, including the mistreatment of the poor, child labour, and the criminal justice system. Oliver$1 (Bs inherent goodness and resilience ultimately lead him to a better life, highlighting themes of morality, redemption, and the power of compassion.s
Keywords: English literature